Humanistic Function Of Religion In Modern Society - Baratova Makhbuba Mubinjanovna (Periodica Journal, 2024)
The article provides a description of the relationship between the concepts of “the idea of humanism” and “religious consciousness” from the standpoint of the foundations and initial principles of a secular state. Based on the normative and legal aspects of freedom of conscience, the tasks of ensuring a harmonious combination of secular knowledge and forms of manifestation of religious faith in the context of interethnic harmony and interfaith peace are considered, where the main factor in the system of implementing the principles of tolerance and humanism is the lifeaffirming idea of building a truly people’s state
Keywords: secular state; religious consciousness